Computational design and fabrication of a novel bioresorbable cage for tibial tuberosity advancement application. (January 2017) - Castilho, Miguel; Rodrigues, Jorge; Vorndran, Elke; Gbureck, Uwe; Quental, Carlos; Folgado, João; Fernandes, Paulo R.
Abstract: Tibial tuberosity advancement (TTA) is a promising method for the treatment of cruciate ligament rupture in dogs that usually implies the implantation of a titanium cage as bone implant. This cage is non-biodegradable and fails in providing adequate implant-bone tissue integration. The objective of this work is to propose a new process chain for designing and manufacturing an alternative biodegradable cage that can fulfill specific patient requirements. A three-dimensional finite element model (3D FEM) of the TTA system was first created to evaluate the mechanical environment at cage domain during different stages of the dog walk. The cage microstructure was then optimized using a topology optimization tool, which addresses the accessed local mechanical requirements, and at same time ensures the maximum permeability to allow nutrient and oxygen supply to the implant core. The designed cage was then biofabricated by a 3D powder printing of tricalcium phosphate cement. This work demonstrates that the combination of a 3D FEM with a topology optimization approach enabled the design of a novel cage for TTA application with tailored permeability and mechanical properties, that can be successfully 3D printed in a biodegradable bioceramic material. These results support the potential of the design optimization strategy and fabrication method to the development of customized and bioresorbable implants for bone repair.